IMPLEMENTASI AUGMENTED REALITY PADA MENU RUMAH MAKAN - Viktor Handrianus Pranatawijaya (Universitas Palangka Raya, 2020)
The menu provided at restaurant can only be seen from a menu book that is shown by the waiter who shows the menu names in the form of text along with the price. This menu book model is felt to be less effective and less attractive. With a restaurant menu application with technology augmented reality, customers will find detailed information about the menu in restaurant displayed in the form of interesting 3D objects. The research method used for software development is Waterfall Model. Application development in this study uses the Unity3D, Vuporia, game engine and Blender3D. The resulting application can be used on Android Smartphones with a minimum operating system of 5.1 (Lollipop). In this case the method used is marker based tracking which is a tracking method using markers or images. From the results of black-box testing, the functional test results show that the application has run as expected, and the results of this application questionnaire get the very good category because it is at a percentage of 87% of the seven statements with likert method and has no problems when run.